Mechanical Experiments and ABAQUS Simulations of Fiber–Coal Gangue Stabilized Expansive Soil Under Freeze–Thaw Cycles - Yan Zhang; Xiupeng Jia; Minglei Wang (Advances in Civil Engineering)
Considering the environmental protection and infrastructure needs for solid waste recycling and improvement of soil engineering properties, a fiber–gangue composite soil consolidation material is proposed to improve the mechanical properties of expansive soils and the workability to resist freeze–thaw (FT) cycling effects. The unconfined compressive strength (UCS) of the expansive soil was measured at varying FT cycles. Then, thermal–mechanical field simulation using Advanced Simulation for Engineering and Sciences (ABAQUS) numerical simulation software was conducted to analyze the stress–strain behavior of the model and compared with the UCS test results obtained during the laboratory test. After that, the microstructural characteristics of modified soil systems after FT cycles were carried out using scanning electron microscope (SEM) mapping to obtain the reinforcement mechanism. The investigation results indicate that the UCS of the modified expansive soil (MES) not only increased after experiencing 12 FT cycles, but also demonstrated a 20.1% reduction in UCS inhibition by the improver compared to plain-expansive soil (PES). Therefore the addition of fiber–coal gangue composite effectively amends the effect of FT cycles on the UCS of expansive soil. UCS test results suggest that a reasonable 9 mm long 0.3% fiber and 20% coal gangue ratio of the composite modifier is advantageous to the soil’s mechanical properties. ABAQUS numerical simulations results the UCS strength of the specimens deteriorates gradually with the increase in the number of FT cycles, which is in agreement with the laboratory measured values. From the SEM observation, the PES samples were loose and the pores increased, while the coal gangue and the fibers of the incorporated expansive soil particles formed links between them, the structure was tight, the pores and cracks were reduced, and the compactness was improved.